Spectrophotometric Determination of Loratadine in Syrup and Study Viscosity Conductivity and Thermodynamic of Binary Mixed Systems of Surfactants with Loratadine" - Eman Thiab Al Samarraee (Journal of Global Pharma Technology, 2019)
A simple, rapid and highly accurate UV spectrophotometric and one viscosity and conductivity methods for estimation of Loratadine in bulk and its pharmaceutical preparation. The method based on using direct ultraviolet detection on the wavelength range 190-400 nm. An absorption maximum was found to be at 286 nm. The percentage recovery of Loratadine ranged from 100.113 to 99.564 % in pharmaceutical syrup form. The developed method was validated with respect to linearity, accuracy (recovery), precision, limit of detection (LOD), limit of quantitation (LOQ), Sandell's sensitivity, molar absorbtivity, molar extinction coefficient and specificity. Beer's law was obeyed in the concentration range of 5-35 μg/mL having line equation y = 0.0248x+ 0.0621 with correlation coefficient of 0.9988.Then studied the factors affecting the formation of wormlike micelles through focusing of different concentrations of Lor. 100-1000 µg.ml-1 in different temperatures (298.15, 303.15, 308.15 and 313.15 K) and at ratios of (20/80, 30/70 and 40/60).Thermodynamic functions (∆Go, ∆Ho, ∆So) were calculated for the process of micelles formation in the presence of Lor., the results indicated that the cationic (CTAB) and anionic (SDS) surfactants revealed a big tendency towards formation of wormlike micelles in Lor. Because intermolecular interactions. The other aspect included The prepared mixtures of surfactants have been study electrochemically using conductometric measurements in the aim of obtaining a relationship between conductivity (L(μS.cm-1)) and viscosity (η (pa.s)) of these solutions, but there is no linear relationship  has been achieved.Keywords: Loratadine, Surfactant, Viscosity and conductivity.